(untitled) (The Batuk, 2025)
This article explores how the hashtag united Nepali people against the hegemonic attitude of India by analyzing the tweets with hashtag (#) BackOffIndia to expose how this hashtag worked as a platform for horizontal connectivity and dissemination of information, citizen journalism, pervasive nature of power and multiple resistance sites. The analytical study of the blockade conducted with the help of a digital platform Twitter (now X) led to the direction that the Indian Government had imposed a state of blockade on Nepal in denial of the promulgation of the constitution in 2015. From the analysis, Twitter has been found useful and an easier and successful tool to spread the voice of protest across the world.